Foreword: The Final Installment - Samantha Adams Becker; Sean M. Leahy (Arizona State University, 2021)
This final installment of the ShapingEDU special issue was inspired by the concept of a "sibling" body of work to compliment the first publication installment. The themes of both bodies of work overlap in their calls to action, yet each article stands solidly on their own. Educators, learning designers, and education leaders have felt the responsibility of helping to usher in the right solutions that will spur student engagement, inclusion and success. Eleven articles unpack the various intertwined journeys we must embark on together to bolster digital equity and inclusion, to recognize all forms of learning and to spur an even more harmonious connections between our institutions and the workforce of the future.